Write a mathematical proof of the algebraic equivalence of (pq)r and (qr)p.

 Jun 3, 2018

We use the associative property of multiplication, which is: x*(y*z)=(x*z)*y.

So, here we have: (pq)r and (qr)p.


It doesn't matter where the brackets are around the numbers, it is still going to yield the same value.


Here's an example: 2,3,4


We have (2*3)*4=(3*4)*2=6*4=12*2


24=24, yay!


 Jun 3, 2018

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.